LzSCL9, a Novel GRAS Transcription Factor in Lanzhou Lily (Lilium davidii var. unicolor), Participates in Regulation of Trichokonins-Primed Heat Stress Tolerance - Xing Cao; Liping Ding; Jiahui Liang; Yanrong Zhou; Xiulan Chen; Haiyan Li; Tao Liu; Wenxiu Yue; Juanjuan Sui; Liangbao Jiang; Yulian Qian; Dongdong Yang; et al. (Plants, 2024)
In our previous research, we found that trichokonins’ (TKs) employment improved the thermotolerance of the Lanzhou lily, a renowned edible crop species endemic to China that is relatively susceptible to high temperatures (HTs). Here, a novel Lanzhou lily GRAS gene, LzSCL9, was identified to respond to heat stress (HS) and HS+TKs treatment based on transcriptome and RT-qPCR analysis. TKs could improve the upregulation of LzSCL9 during long-term HS. The expression profile of LzSCL9 in response to HS with or without TKs treatment showed a significant positive correlation with LzHsfA2a-1, which was previously identified as a key regulator in TKs’ conferred resilience to HT. More importantly, overexpression of LzSCL9 in the lily enhanced its tolerance to HTs and silencing LzSCL9 in the lily reduced heat resistance. Taken together, this study identified the positive role of LzSCL9 in TK-induced thermotolerance, thereby preliminarily establishing a molecular mechanism on TKs regulating the thermostability of the Lanzhou lily and providing a new candidate regulator for plant heat-resistant breeding.